Clima escolar e transtornos mentais comuns em professores do ensino técnico de nível médio privado - Filippsen, Osvaldo André (Universidade do Vale do Rio dos Sinos, 2019)
Common mental disorders, according the International Labor Organization, presenting highest incidence among workers, including teachers. In this direction, the present thesis addressed the theme relating it to the perception of school climate. It´s organized in two empirical studies of quantitative approach. In the first one, we tried to characterize and compare the school climate perceived by teachers and students of the technical teaching of private secondary level, finding that both perceived as positive the factors teacher-student relations, student-student relations and bullying. Separately, teachers also point-ed as positive the clarity of expectations and school safety. The other factors received negative evaluations. There was a difference in the teachers and students perception of the school climate in all factors, except for the student-student relations. The second study, in turn, examined whether there was contribution and to what extent the school climate affected common mental disorders (CMD) among teachers. The results indicat-ed the presence of normal to mild CMD for most participants, and weak correlations with school climate factors. However, it was found that the negative perception of jus-tice in the rules explained 16% of the variance of depression and 15% of stress, while negative perception of safety explained the anxiety variance by 14%. It´s believed that the discussion of the data might help managers and teachers to understand the environ-ment in which they work to seek the possible influences they exert in the development of mental disorders, aiming at prevention and health promotion in this context.
Keywords: Clima escolar; Transtornos mentais comuns; Professores e estudantes; School climate; Common mental disorders; Teachers and students; ACCNPQ::Ciências Humanas::Psicologia